Revisiting the voices from the Margins: A Study of Subaltern Narrative in Amitav Ghosh’s The Calcutta Chromosome - Sharma, Shyam Prasad (Dhaulagiri Journal of Contemporary Issues, 2024)
The Calcutta Chromosome by Amitav Ghosh delves into the subaltern narrative giving voice to marginalized people often overlooked in mainstream literature. The narrative draws on the themes of identity, power, and history through its characters and their experiences challenging traditional narratives and offers a unique perspective on the complexities of colonialism, science, and storytelling. The novel resurfaces the issues of defiance and resistance against the imperial power and its’ hegemony as depicted by Ghosh through the characters like Murugan, Mangala and Laakhan against British scientist Roland Ross and his associates. In the juncture of scientific research about the Malaria in colonial India, Ronald Ross was assisted by the Indian people, however, their contribution remained excluded in colonial historiography which Ghosh's narrative stages to revisit the colonizer's discriminatory policy. Meantime, this study triggers on the voice of the voiceless to subvert the 'orientalism' in Westerners' historiography by staging the voice of the oppressed in the domain of subaltern studies envisaged by Spivak and others. In so doing, it valorises the voice the subalterns by constituting an academic discourse for their age-longed muffled silence.